POLICY OF GIVING IMPUNITY TO STATE ADMINISTRATORS IN THE FIELD OF FISCAL AND MONETARY POLICY IN LAW NUMBER 2 YEAR 2020 - Afif Noor (Journal Philosophy of Law, 2022)
To create economic and financial stability due to the Covid-19 pandemic, the government stipulates Perppu No. 1 of 2020 becomes Law No. 2 of 2020. The law states that state officials in the field of Fiscal and Menoter Policies cannot be prosecuted civilly or criminally in carrying out their duties and official decisions in the context of implementing the Perppu are not objects of state administrative lawsuits. Whereas in a state of law everyone has a position without exception. This research is classified as normative juridical using library materials as the main data source. Based on the research, the policy has the potential to cause a moral hazard, adverse selection, and abuse of power and is contrary to the principles of Good financial governance. The policy of granting impunity to state administrators in the fiscal and monetary fields is contrary to the principle of equality before the law which is constitutionally stated in the 1945 Constitution.